Social Media Engagement: What Motivates User Participation and Consumption on YouTube in Nepal - Luintel, Nishan (Nepalese Journal of Economics, 2025)
This study examines the impact of social media engagement: What motivates user participation and consumption on YouTube in Nepal. User engagement metrics are the dependent variable. Likewise, the selected independent variables are content type, video length, frequency of uploads, interaction with viewers, and visual appeal. The primary source of data is used to assess the opinions of the respondents regarding these variables in the context of YouTube in Nepal. The study is based on primary data with 17 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. Descriptive statistics, Kendall’s Tau correlations, and regression models are estimated to test the significance and importance of these factors on user engagement metrics on YouTube in Nepal. The study showed that content type has a positive impact on user engagement metrics on YouTube. It implies that varied and interesting content leads to increased user engagement. The result also showed that video length has a positive impact on user engagement metrics. It implies that optimal video length leads to increased user engagement. Moreover, frequency of uploads has a positive impact on user engagement metrics. It implies that regular uploads lead to increased user engagement. Furthermore, interaction with viewers has a positive impact on user engagement metrics, indicating that active interaction leads to increased user engagement. Similarly, the result also showed that visual appeal has a positive impact on user engagement metrics. It indicates that visually appealing videos lead to increased user engagement. The result also showed that improved visual appeal leads to increased user engagement on YouTube.